2020
DOI: 10.3389/fvets.2020.00415
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Probiotic Properties of Lactobacillus salivarius Isolated From Chickens as Feed Additives

Abstract: The continued use of sub-therapeutic antibiotics as feed additives in the poultry industry improved health and growth performance. However, the resulting antibiotic resistance increasingly becomes a major threat to public health. Probiotics are promising alternatives for the antibiotics used in poultry industry. The aim of this study was to evaluate the probiotic properties of Lactobacillus salivarius as feed additive in chickens. White leghorn chickens were randomly assigned to experimental groups. Effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 32 publications
3
37
0
2
Order By: Relevance
“…Correlation analyses of IGF2BP1 expression and cecal microbes showed that IGF2BP1 was significantly associated with microbes, such as Lactobacillus , more specifically, Lactobacillus salivarius , which were highly abundant in HWS. As a growth promoter, Lactobacillus salivarius additives could increase the size and weight of young animals, such as chickens ( 59 , 60 ), mice ( 61 ), and pigs ( 62 ). Meat-type chickens fed a Lactobacillus salivarius mixture isolated from their intestines increased populations of beneficial bacteria, such as Lactobacillus and Bifidobacterium in the intestine and, thus, increased body weight ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analyses of IGF2BP1 expression and cecal microbes showed that IGF2BP1 was significantly associated with microbes, such as Lactobacillus , more specifically, Lactobacillus salivarius , which were highly abundant in HWS. As a growth promoter, Lactobacillus salivarius additives could increase the size and weight of young animals, such as chickens ( 59 , 60 ), mice ( 61 ), and pigs ( 62 ). Meat-type chickens fed a Lactobacillus salivarius mixture isolated from their intestines increased populations of beneficial bacteria, such as Lactobacillus and Bifidobacterium in the intestine and, thus, increased body weight ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Cu/Zn-Pal-1 supplementation in the CZPS group significantly enhanced the proportion of Ligilactobacillus compared with the SAL group; it seems that Cu/Zn-Pal-1 reduces the S. Typhimurium load in the gut to avoid the effects of Salmonella on these taxa. Besides, it has been previously reported that Ligilactobacillus has immunomodulatory capabilities and protects chickens against E. coli O78 colonization ( Masumizu et al, 2019 ; Wang et al, 2020 ). This suggests that the increase in the relative abundance of Ligilactobacillus in the CZPS group may further protect chickens against Salmonella colonization in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…An undeniable feature of probiotic use is the broad spectrum of applications that have resulted in positive animal performance outcomes. Increases in egg and milk production, gut health and disease reduction, leg health and lameness reduction, reproductive health, meat quality and metabolic homeostasis, have all been demonstrated experimentally following feed supplementation with probiotics (Mountzouris et al 2010;Wideman et al 2012;Shini et al 2013Shini et al , 2020bZheng et al 2014Zheng et al , 2016Latorre et al 2015;Bajagai et al 2016;Angelakis 2017;Gadde et al 2017;Cameron and McAllister 2019;Park et al 2020;Wang et al 2020;Zommiti et al 2020). Together, this is a very strong endorsement for the role of probiotics in promoting gut health, and animal health and productivity.…”
Section: Box 1 Necrotic Enteritismentioning
confidence: 96%